Efficient Generation of Large‐Fragment Knock‐In Mouse Models Using 2‐Cell (2C)‐Homologous Recombination (HR)‐CRISPR. Issue 1 (8th January 2020) - Gu, Bin; Posfai, Eszter; Gertsenstein, Marina; Rossant, Janet
Abstract: Generating large‐fragment knock‐ins, such as reporters, conditional alleles, or humanized alleles, directly in mouse embryos is still a challenging feat. We have developed 2C‐HR‐CRISPR, a technology that allows highly efficient (10‐50%) and rapid (generating founders in 2 months) targeting of large DNA fragments. Key to this strategy is the delivery of CRISPR reagents into 2‐cell‐stage mouse embryos, taking advantage of the high homologous recombination activity during the long G2 cell cycle phase at this stage. Furthermore, by exploiting a Cas9–monomeric streptavidin (Cas‐mSA) and biotinylated PCR template (BioPCR) system to localize the repair template to specific double strand breaks, the efficiency can be further improved to up to 95%. Here we provide a procedure to generate large‐fragment knock‐in mouse models using 2C‐HR‐CRISPR. We first describe the principles for designing single guide RNAs and repair templates but refer to published manuscripts and protocols for molecular cloning methods or commercial sources for these reagents. We then describe two unique aspects of 2C‐HR‐CRISPR that are critical for success: (1) production of the CRISPR reagents for 2C‐HR‐CRISPR, particularly for applying the Cas9‐mSA/BioPCR method, and (2) microinjection of mouse embryos at the 2‐cell stage. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Single guide RNA and repair template design Basic Protocol 2 : Preparing reagents for 2C‐HR‐CRISPR Basic Protocol 3 : Microinjecting 2‐cell‐stage mouse embryos